Aturan Pembatasan Perizinan Keluar Asrama Bagi Mahasiswa dalam Tinjauan Kaidah Sadd Al-Żarī‘ah (Studi Kasus di Asrama Putra STIBA Makassar): Regulations on Restrictions of Dormitory Exit Permits for Students in Light of the Principle of Sadd Al-Żarī‘ah (a Case Study at the Male Dormitory of STIBA Makassar) - Ahmad Syaripudin; Hamzah Sekkeng (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to examine the implementation of exit permit restrictions for students at the STIBA Makassar male dormitory and analyze it through the lens of the uṣūl fiqh principle of sadd al-żarī‘ah. The research responds to the contemporary challenge of character decline among youth, for which the boarding school system is seen as a strategic solution. The exit permit policy is part of efforts to enhance student character development. Using a qualitative field research method with Normative, uṣūl fiqh, and case study approaches, data were collected through interviews, observation, and analysis of both classical Islamic sources and modern literature. The findings show that the restriction is outlined in the Student Code of Ethics and categorized into three levels: absolute restriction, conditional permission, and unconditional permission. However, violations have been identified, including misuse of permits for activities that contradict Islamic values, exceeding the permitted time limits, and unauthorized methods of leaving the dormitory such as falsifying documents or climbing over fences. From the perspective of the uṣūl fiqh principle of sadd al-żarī‘ah, the policy is considered appropriate as a preventive measure to close the pathways that may lead to moral, academic, and disciplinary harm. It is viewed as a means of protecting student well-being and supporting the success of character formation within the dormitory environment.